Global changes in the rat heart proteome induced by prolonged morphine treatment and withdrawal - Drastichova, Zdenka; Skrabalova, Jitka; Jedelsky, Petr; Neckar, Jan; Kolar, Frantisek; Novotny, Jiri (PloS one, 2012)
Morphine belongs among the most commonly used opioids in medical practice due to its strong analgesic effects. However, sustained administration of morphine leads to the development of tolerance and dependence and may cause long-lasting alterations in nervous tissue. Although proteomic approaches enabled to reveal changes in multiple gene expression in the brain as a consequence of morphine treatment, there is lack of information about the effect of this drug on heart tissue. Here we studied the effect of 10-day morphine exposure and subsequent drug withdrawal (3 or 6 days) on the rat heart proteome. Using the iTRAQ technique, we identified 541 proteins in the cytosol, 595 proteins in the plasma membrane-enriched fraction and 538 proteins in the mitochondria-enriched fraction derived from the left ventricles. Altogether, the expression levels of 237 proteins were altered by morphine treatment or withdrawal. The majority of changes (58 proteins) occurred in the cytosol after a 3-day abstinence period. Significant alterations were found in the expression of heat shock proteins (HSP27, α-B crystallin, HSP70, HSP10 and HSP60), whose levels were markedly up-regulated after morphine treatment or withdrawal. Besides that morphine exposure up-regulated MAPK p38 (isoform CRA_b) which is a well-known up-stream mediator of phosphorylation and activation of HSP27 and α-B crystallin. Whereas there were no alterations in the levels of proteins involved in oxidative stress, several changes were determined in the levels of pro- and anti-apoptotic proteins. These data provide a complex view on quantitative changes in the cardiac proteome induced by morphine treatment or withdrawal and demonstrate great sensitivity of this organ to morphine.
Keywords: HSP27 Heat-Shock Proteins; chaperon hsp60; Substance Withdrawal Syndrome; Male; Rats, Wistar; chaperonin 10; Chaperonin 60; proteiny tepelného šoku HSP70; HSP70 Heat-Shock Proteins; závislost na morfiu; Morphine Dependence; Morphine; proteom; Myocardium; mužské pohlaví; potkani Wistar; proteiny tepelného šoku HSP27; krysa rodu Rattus; abstinenční syndrom; Animals; morfin; Crystallins; zvířata; Chaperonin 10; Rats; krystaliny; Proteome; myokard